Transplantação cardíaca: cinco anos de actividade - Antunes, MJ (2010)
OBJECTIVE: To analyze the initial five years experience of the new heart transplant program of Coimbra University Hospitals. METHODS: Between November 2003 aid December 2008, 132 patients were transplanted, with a mean age of 52.0 years (range 3-71 years), of whom 98 were male (74%). Half of the patients had dilated cardiomyopathy and 33% ischemic cardiomyopathy. The mean age of donors was 31.7 years and 102 were male (77%). Donor hearts were harvested at a distance in 62% of cases. There was a gender mismatch between donor and recipient (F:M) in 19% of cases and ABO blood type disparity (not identical but compatible) in 11%. In all cases we used the technique of total transplantation with bicaval anastomosis, modified in this center. Mean ischemia time was 88.9 +/- 32.2 minutes. All patients received induction therapy with basiliximab and methylprednisolone. RESULTS: Six patients (4.5%) died within 30 days or during hospitalization, due to graft failure in four and hyperacute rejection in two. Two patients required prolonged ventilation, ten (8%) required inotropic support for more than 48 hours, and four required pacemaker implantation. Mean hospital stay was 15.6 +/- 15.2 days (median 13 days). Ninety percent of patients (116/129) were maintained on triple immunosuppressive therapy, including cyclosporine, the remainder receiving tacrolimus. In 23 patients it was necessary to change the immunosuppressive regimen due to renal and/or tumoral complications, or humoral rejection. All patients are followed regularly in the Surgical Center. Thirteen patients (10%) died late of cancer (6 patients), infection (4 patients), and pancreatitis, pulmonary hypertension and suicide (one patient each). Twenty-two patients (17%) had 25 episodes of cellular rejection (> or = 2R), with clinical consequences in only one case, and five had humoral rejection (3.9%). No patients died of late rejection, but there is evidence of mild graft vascular disease in one. Actuarial survival (Kaplan-Meier) at one and five years was 90% and 82%, respectively. CONCLUSION: In this initial series of five years we obtained results equivalent to or bette than those in centers with wider and longer experience, aided by self-correction arising from our own experience. This program has increased the rate of cardiac transplantation in Portugal to above the European average.